ISOLASI BAKTERI PENDEGRADASI MINYAK /LEMAK DARI BEBERAPA SEDIMEN PERAIRAN TERCEMAR DAN BAK PENAMPUNGAN LIMBAH - I W. Budiarsa Suyasa (Bumi Lestari Journal of Environment)
Active mud represent process processing of biology by aerobic by using system ofsuspended growth. Microorganism staying in form of suspended referred also solidsuspended liquor mixed ( SSLM), work by fastening organic substrate later thenelaborating it with enzyme of exocelluler so that become its dissolve. Process resolving ofcompounds of organic, microorganism get the source of and carbon of energy. Mudsuspended conducted by 1 g follow the example of Mud or sediment thinned withphysiological condensation ( 8,5 NaCl g / L) and dissolve up to 10-4 ,or can be conductedby taking 0,5 g of sediment into tube reaction of containing 4,5 physiological saltcondensation then shake to get homogeneous suspended. suspended and disseminated bycontaining solder cup on specific media, and then incubation at temperature 270C during24 - 48 hour. Obtained by isolate of RPH1,RPH2, PP, SBDG and STT. During process ofseeding measured parameters, there are VSS and COD that measured base on timeduring treatment. Its process was result RPH2 isolate that showing higher growth ofmicrobiologist activity then another. Result of the research showing that VSS and CODhas highest during treatment.